Contemporary Public Policy Issues in Industrial Relations - Hall, Noël (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
The present system of collective bargaining is more an exercise in the use of coercive economic and political power by labour and management than a process of rational, logical argument and existing conciliation procedures have proven inadequate in reflecting the public interest in dispute settlement. What then is the impact of B.C. Bill 33 ?